The Roman Shipwreck of Antirhodos Island in the Portus Magnus of Alexandria, Egypt. (16th October 2012) - Sandrin, Patrice; Belov, Alexander; Fabre, David
<x xml:space="preserve">Abstract</x> Between 1998 and 1999 three excavation campaigns were undertaken on a shipwreck at the now‐submerged site of the ancient Portus Magnus, off the coast of Alexandria. The site, close to the island of Antirhodos, was identified through geophysical and archaeological surveys carried out by the Institut Européen d'Archéologie Sous‐Marine (IEASM), directed by Franck Goddio. The remains of the ship lie c.5 m deep and are spread over c.350 sqm. No cargo has been found. Artefacts recovered, the details of the ship's architecture and radiocarbon dating all suggest it sunk between the end of the 1st century BCE and the 1st century CE. Its dimensions correspond to those of commercial ships of the Roman era. Identification of the wood used contributes significantly to our knowledge of materials used in naval architecture of this period.